Highly Efficient Aluminum Trichloride Catalyzed Michael Addition of Indoles and Pyrroles to Maleimides - An, Yu-Long; Shao, Zhi-Yu; Cheng, Jian; Zhao, Sheng-Yin (Synthesis, 2013)
A highly efficient synthetic strategy for Michael addition of indoles and pyrroles to maleimides has been developed using the Lewis acids zinc chloride or aluminum trichloride as the catalyst. The reactions generated 3-substituted indoles and 2-substituted pyrroles in high yields with excellent regioselectivity in the presence of a catalytic amount of zinc chloride or aluminum trichloride under mild reaction conditions. The method is simple, efficient, and practical.
Keywords: Michael addition; indole; pyrrole; maleimide; aluminum trichloride